Etika Bisnis dalam Perspektif Islam - Abdul Ghafur (Fakultas Ekonomi dan Bisnis Islam, 2018)
In 1997-1998 Indonesia experienced a monetary crisis and economic crisis, where one of the factors causing it is the existence of economic wideenization. The image arises because the business ethics of entrepreneurs in Indonesia is low. If analyzed more deeply, the phenomenon is called the term